2014
DOI: 10.1097/igc.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologic Cancer InterGroup (GCIG) Consensus Review for Squamous Cell Carcinoma of the Ovary

Abstract: Squamous cell carcinoma of the ovary is a rare complication of mature cystic teratoma. The epidemiology, pathology, diagnosis, and management of this rare tumor are reviewed. Clinical characteristics, preoperative imaging, and tumor markers may help to predict malignancy preoperatively. Complete cytoreduction should be the aim of surgery. The prognosis for stage 1A disease is good, but for women with advanced or recurrent disease, it is very poor and has not improved in recent years. At present, there are insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…reported that SCC antigen, CEA and CA125 were most frequently raised serum markers. SCC antigen was elevated in 81% of ovarian SCC cases, while CEA was elevated in 65% and CA125 was elevated in 60% . Hypercalcemia is also reported in patients with SCC, and was detected in our case of ovarian SCC using zoledronic acid.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…reported that SCC antigen, CEA and CA125 were most frequently raised serum markers. SCC antigen was elevated in 81% of ovarian SCC cases, while CEA was elevated in 65% and CA125 was elevated in 60% . Hypercalcemia is also reported in patients with SCC, and was detected in our case of ovarian SCC using zoledronic acid.…”
Section: Discussionsupporting
confidence: 55%
“…We report here a case of malignant change from an ovarian mature cystic teratoma. The estimated incidence of SCC arising from ovarian mature cystic teratomas is 0.2–0.8% . From September 2013 to September 2017, only two cases of malignant change from ovarian mature cystic teratoma were diagnosed at our institution.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Due to their rarity, there are few large published series and no prospective clinical trials in MCT-derived SCC, and the recent Gynecologic Cancer Intergroup (GCIG) consensus review concluded that there were insufficient data to provide clear guidance on optimal treatment (7). However, the prognosis for these SCC is poor, especially for stage II -IV disease [summarised in (6)].…”
Section: Introductionmentioning
confidence: 99%